Modeling Vector Fields in Space of Affine Connection (Моделювання, керування та інформаційні технології, 2019)
The authors have been constructed the splitting of the basic geometric images vector field (points, straights, hyperplanes and hyperguadrics) in transition from n-dimensional affine space to the space of affine connection. All invectigations have been fulfilled in the moving coordinate system of zero order.